2023
DOI: 10.3390/plants12071495
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling, Biological Activities, and In Silico Molecular Docking Studies of Causonis trifolia (L.) Mabb. & J.Wen Shoot

Abstract: Causonis trifolia (L.) Mabb. & J.Wen, commonly known as “fox grape”, is an ethnomedicinally important twining herb of the Vitaceae family, and it is used by ethnic communities for its wide range of therapeutic properties. Our research aims to investigate the chemical composition; antioxidant, anti-inflammatory, and antidiabetic activities; and mechanisms of interaction between the identified selective chemical compounds and the target proteins associated with antioxidant, anti-inflammatory, and antidiabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The study of Tadesse et al [ 27 ] revealed that blanching temperatures from raw to 90 °C led to different total phenolic content in dawrach ( Raphanus raphanistrum L.), in which the highest amount was detected in samples with 70 °C treatment. Hazra et al [ 28 ] reported that the interaction of temperature, solvent and extraction time affected the available phenolic content in Causonis trifolia (L.) Mabb. & J. Wen, an herb.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Tadesse et al [ 27 ] revealed that blanching temperatures from raw to 90 °C led to different total phenolic content in dawrach ( Raphanus raphanistrum L.), in which the highest amount was detected in samples with 70 °C treatment. Hazra et al [ 28 ] reported that the interaction of temperature, solvent and extraction time affected the available phenolic content in Causonis trifolia (L.) Mabb. & J. Wen, an herb.…”
Section: Discussionmentioning
confidence: 99%